2017
DOI: 10.1016/j.jtcvs.2017.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac reprogramming factor Gata4 reduces postinfarct cardiac fibrosis through direct repression of the profibrotic mediator snail

Abstract: Objective The administration of a variety of reprogramming factor cocktails has now been shown to reprogram cardiac fibroblasts into induced cardiomyocyte-like cells (iCMs). Reductions in ventricular fibrosis observed after reprogramming factor administration, however, seem to far exceed the extent of iCM generation in vivo. We therefore investigated whether reprogramming factor administration might primarily play a role in activating anti-fibrotic molecular pathways. Methods Adult rat cardiac fibroblasts (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Not only, EZH2 represses gene through histone modification, but also methylates non-histone protein such as Gata-binding protein 4 (GATA4) [31]. GATA4 is a key transcription factor of heart development [32] and regulator of fibrosis [33]. GATA4 methylation by polycomb repressive complex (PRC) 2 results in reduced GATA4 transcriptional potency [31], indicating a potential additional role of EZH2 decrease in the cardiac fibrosis induced by maternal high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Not only, EZH2 represses gene through histone modification, but also methylates non-histone protein such as Gata-binding protein 4 (GATA4) [31]. GATA4 is a key transcription factor of heart development [32] and regulator of fibrosis [33]. GATA4 methylation by polycomb repressive complex (PRC) 2 results in reduced GATA4 transcriptional potency [31], indicating a potential additional role of EZH2 decrease in the cardiac fibrosis induced by maternal high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways and regulatory mechanisms that are active during embryogenesis and are involved in heart growth and development may be used to repair the injured adult heart . The overexpression of cardiac GATA4 protein preserves cardiac function after cardiac injury by promoting increased angiogenesis and reduced fibrosis . Moreover, genetic enhancement of GATA4 protein was able to prevent cardiomyocyte apoptosis and drug‐induced cardiotoxicity .…”
Section: Gata4 Structure and Functionmentioning
confidence: 99%
“…7 The overexpression of cardiac GATA4 protein preserves cardiac function after cardiac injury by promoting increased angiogenesis and reduced fibrosis. [41][42][43] Moreover, genetic enhancement of GATA4 protein was able to prevent cardiomyocyte apoptosis and drug-induced cardiotoxicity. 44 A study by Malek Mohammadi et al demonstrated that high abundance of cardiac GATA4 by adenoviral gene transfer at postnatal days 1-7 markedly improved cardiac regeneration after cryoinjury and rescued the loss of regenerative capacity.…”
mentioning
confidence: 99%
“…Mathison et al 94 recently reported that Gata4 has antifibrotic function through downregulation of the profibrotic transcription factor Snail. They demonstrated that Gata4 expression alone is sufficient to decrease post-infarct cardiac fibrosis in a rat ligation model.…”
Section: Fibrosis and Tgf-β Signalingmentioning
confidence: 99%
“…They suggest incorporation of Gata4 into reprogramming cocktails in vivo. 94 Further characterization of the function of Gata4 is necessary to elucidate mechanisms of improved cardiac function separate from its reprogramming effects.…”
Section: Fibrosis and Tgf-β Signalingmentioning
confidence: 99%